Surgical quality in organ procurement during day and night: an analysis of quality forms. Issue 11 (25th November 2018) - de Boer, Jacob; Van der Bogt, Koen; Putter, Hein; Ooms-de Vries, Kirsten; Haase-Kromwijk, Bernadette; Pol, Robert; De Jonge, Jeroen; Dejong, Kees; Nijboer, Mijntje; Van der Vliet, Daan; Braat, Dries
Abstract : Objectives: To analyse a potential association between surgical quality and time of day. Design: A retrospective analysis of complete sets of quality forms filled out by the procuring and accepting surgeon on organs from deceased donors. Setting: Procurement procedures in the Netherlands are organised per region. All procedures are performed by an independent, dedicated procurement team that is associated with an academic medical centre in the region. Participants: In 18 months' time, 771 organs were accepted and procured in The Netherlands. Of these, 17 organs were declined before transport and therefore excluded. For the remaining 754 organs, 591 (78%) sets of forms were completed (procurement and transplantation). Baseline characteristics were comparable in both daytime and evening/night-time with the exception of height (p=0.003). Primary outcome measure: All complete sets of quality forms were retrospectively analysed for the primary outcome, procurement-related surgical injury. Organs were categorised based on the starting time of the procurement in either daytime (8:00–17:00) or evening/night-time (17:00–8:00). Results: Out of 591 procured organs, 129 organs (22%) were procured during daytime and 462 organs (78%) during evening/night-time. The incidence of surgical injury was significantly lower during daytime; 22 organs (17%) compared with 126 organs (27%) procured during evening/night-time (p=0.016). This association persists when adjusted for confounders. Conclusions: This study shows an increased incidence of procurement-related surgical injury in evening/night-time procedures as compared with daytime. Time of day might (in)directly influence surgical performance and should be considered a potential risk factor for injury in organ procurement procedures.